Factors that influence the decision to undergo labiaplasty: Media, relationships, and psychological well-being - Sharp, Gemma; Tiggemann, M.; Mattiske, J. (Oxford University Press, 2016)
Background: An increasing number of women are undergoing labiaplasty procedures; however, very little is known about the psychological factors that motivate women to seek out this procedure. Objectives: To investigate the factors that influence women's decisions to undergo labiaplasty. Methods: Women seeking to undergo labiaplasty (n = 35) were compared with women who were not (n = 30). Standardized measures were employed to assess the patients' media exposure (television, the Internet, advertising, pornography), relationship quality, and psychological well-being. Results Women's motivations for deciding to undergo a labiaplasty procedure were characterized as “appearance,” “functional,” “sexual,” or “psychological” motivations, with concerns about the labia's appearance being the most commonly reported motivation. Correspondingly, women seeking labiaplasty were significantly less satisfied with the appearance of their genitals than the comparison group (P < .001). These women had also experienced greater exposure to images of female genitalia on the Internet (P = .004) and in advertisements (P = .021), and had internalized these images to a greater extent (P = .010). There were no differences between the two groups on the measures of relationship quality. However, significantly fewer of the women seeking to undergo a labiaplasty procedure were involved in a romantic relationship at the time of the study (P = .039). There were also no differences between the two groups on the measures of psychological well-being, except that women seeking to undergo labiaplasty were less satisfied with their lives overall (P = .027). Conclusions: The findings identified media exposure and relationship status as important factors that influence women's decisions to undergo labiaplasty.